Aar Paar - Guru Dutt; Abrar Alvi; Nabendu Ghosh; Nayyar, O.P. (New Delhi Moser Baer Entertainment, 2010)
Kalu is a taxi-driver in Bombay, India. He has two women who love him and would like to marry him. Kalu first wants to establish himself, and become rich, before he can even think of marriage. One of the women who loves him, has a father who is involved in gangster-type activities, and would like Kalu also to join him so that he can get rich soon. Kalu has now to decide to become rich quick or sleep better
Shyama, Guru Dutt and Jagdish Sethi
Hindi movies
Copyright Moser Baer
Summary from IMDB.com
NTSE all region with english subtitles
Keywords: Motion picture